Nonprecious‐metal Fe/N/C Catalysts Prepared from π‐Expanded Fe Salen Precursors toward an Efficient Oxygen Reduction Reaction. Issue 4 (21st February 2018) - Tanaka, Yuta; Onoda, Akira; Okuoka, Shin‐ichi; Kitano, Tomoyuki; Matsumoto, Koki; Sakata, Takao; Yasuda, Hidehiro; Hayashi, Takashi
Abstract: The front cover artwork for issue 4/2018 represents research conducted in a collaboration between Osaka University (Japan) and Nippon Shokubai Co., Ltd. (Japan). The image illustrates the preparation of the Fe/N/C catalysts by pyrolysis of π‐expanded Fe(Salen) precursors for the oxygen reduction reaction. See the Full Paper itself at https://doi.org/10.1002/cctc.201701629 . Abstract : "Atomically‐dispersed Fe active sites with a high content of pyridinic N promote the efficient four‐electron reduction of dioxygen." This and more about the story behind the research featured on the front cover can be found in this issue's Cover Profile. Read the full text of the corresponding research athttps://doi.org/10.1002/cctc.201701629 .